2014
DOI: 10.1002/jib.108
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy, copy number variation and unique chromosomal structures in bottom-fermenting yeast revealed by array-CGH

Abstract: DNA microarray for comparative genome hybridization (CGH) of bottom-fermenting yeast was performed based on our in-house DNA sequence data. Aneuploidy, copy number variation and unique chromosomal structures were observed among bottomfermenting yeast strains. Our array experiments revealed a correlation between copy number variation and mRNA expression levels. Chromosomal structures in a Saccharomyces carlsbergensis-type strain and in a S. monacensis-type strain that both belong to S. pastorianus phylogenetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…cerevisiae strains. In general, these alloploid genomes tolerate aneuploidy well, with massive diversity in chromosome copy numbers across strains (23, 125, 126). Some aneuploid lager brewing yeasts even sporulate, albeit at low efficiency, by anomalous cell division (79).…”
Section: Ccnv In Industrial Saccharomyces Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…cerevisiae strains. In general, these alloploid genomes tolerate aneuploidy well, with massive diversity in chromosome copy numbers across strains (23, 125, 126). Some aneuploid lager brewing yeasts even sporulate, albeit at low efficiency, by anomalous cell division (79).…”
Section: Ccnv In Industrial Saccharomyces Yeastsmentioning
confidence: 99%
“…Despite its frequent occurrence, the impacts of aneuploidy in these genetic contexts have not been explored in depth, and it is unclear how AASR and chromosome-specific copy number effects compare to those observed in otherwise euploid S. cerevisiae strains. In general, these alloploid genomes tolerate aneuploidy well, with massive diversity in chromosome copy numbers across strains ( 23 , 125 , 126 ). Some aneuploid lager brewing yeasts even sporulate, albeit at low efficiency, by anomalous cell division ( 79 ).…”
Section: Ccnv In Industrial Saccharomyces Yeastsmentioning
confidence: 99%
“…In S. pastorianus , ploidy differences, copy number variations, and single-nucleotide variants (SNVs) identified by array-CGH 10 , 11 or other approaches have suggested that the Saaz (Group 1) and Frohberg (Group 2) types originated from independent hybridization events, 11 13 a theory that has gained broad acceptance. In contrast, the recent confirmation of two breakpoints associated with interchromosomal translocation of HSP82 and KEM1 genes implies a common origin.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of brewing yeast strains their polyploid nature would be supposed to confer genetic stability ( 119 ) . However, since many are aneuploid ( 139 ) this assumption is incorrect. In fact, although loss of individual chromosomes during cell division would be considered a major and possibly lethal error, it has also been suggested that aneuploidy might provide a route for genetic diversification ( 118 ) .…”
Section: Looking After Your Daughtersmentioning
confidence: 99%